Multifocal motor neuropathy: long-term clinical and electrophysiological features of the disease - D. A. Grishina; N. A. Suponeva; T. A. Tumilovich; M. A. Piradov (Неврология, нейропсихиатрия, психосоматика)
Little attention has been paid abroad to the problem of the long-term course of multifocal motor neuropathy (MMN). In our country, catamnestic studies of MMN have not been conducted at all. However, the results of such an analysis are extremely important for understanding the course and prognosis of the disease.Objective: to analyse the clinical and neurophysiological data of patients with MMN with a disease duration of more than 5 years.Material and methods. The study included 28 patients with MMN: 9 women (32%) and 19 men (68%); the median age at admission was 50 [44; 56] years; the median disease duration was 10 [8; 13] years. Medical documentation, medical history, complaints, neurological examination results (scored on the MRC and INCAT scales) and results of electroneuromyography (ENMG) of the long nerves of the hands were analysed.Results. The median time between onset of the disease and diagnosis was 5.5 [2; 10] years. Paresis <3 points on the MRC scale was found in the extensor muscles of the hand and fingers (12/28; 43%), in the median (15/28; 53%) and ulnar (20/28; 71%) muscle groups of the hands, in the extensors (11/28; 39%) and flexors (9/28; 32%) of the feet. The median total score for the degree of disability on the INCAT scale was 3 [2; 3] for the hands and 1 [0; 2] for the legs. The comparative analysis of the severity of the neurological deficits on the MRC and INCAT scales at the onset of the disease and in the long-term catamnesis revealed no significant differences (p>0.05). An objective assessment of sensory disorders revealed no changes when testing tactile, pain and temperature sensitivity, while half of the cases (14/28; 50%) showed a disturbance of vibration sensitivity in the lower extremities. The ENMG examination was consistent with the electrophysiological criteria of the disease, one third of the patients showed significant secondary damage to the axons of the motor fibers of the hand nerves, and in half of the cases a slight impairment of the axons of the sensory fibers was registered.Conclusion. MMN is a curable disease. Unfortunately, our retrospective analysis showed that in the Russian Federation there are problems with its diagnosis and quality care of this category of patients. Late diagnosis, delayed start of treatment and non-compliance with the schedule of pathogenetic therapy lead to persistent disability of patients.